2014
DOI: 10.1111/hepr.12337
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography during hepatic arteriography pattern may predict hepatocellular carcinoma recurrence following transarterial chemoembolization

Abstract: Patients with pattern 2 hepatocellular carcinoma and/or four or more lesions may have a relatively high recurrence rate after transarterial chemoembolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
1
Order By: Relevance
“…Katayama et al . reported that CMN type showed significantly higher recurrence after TACE 40 . In our study, CMN type showed poor prognosis in the univariate analysis but not in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 60%
“…Katayama et al . reported that CMN type showed significantly higher recurrence after TACE 40 . In our study, CMN type showed poor prognosis in the univariate analysis but not in the multivariate analysis.…”
Section: Discussioncontrasting
confidence: 60%